KEPENTINGAN INDONESIA MELAKUKAN EKSPOR KOMODITI CENGKEH KE SINGAPURA PADA TAHUN 2015-2018 - Nadia Irene Nababan; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Indonesia is the largest clove producer and consumer country in the world. Indonesia's excessive production of cloves each year drives Indonesia to export these clove commodities. The main destination country for Indonesian clove exports is Singapore. In 2012-2014, Indonesia's clove production decreased, but clove commodity exports to Singapore continued to increase. Why did Indonesia export cloves to Singapore in 2015-2018.This study uses a qualitative research method, with the level of analysis of the nation state. The author uses the theory of International Political Economy with the concept of National Interest using the perspective of Liberalism. To analyze this case, the authors collected data from books, journals, websites, dictionaries, reports, data from the Ministry of Trade and the Indonesian Statistics Agency regarding the clove export cooperation between Indonesia and Singapore.The findings of this study indicate that clove exports carried out by Indonesia to Singapore are a way for the country to maintain the continuity of the cooperation between Singapore and Indonesia. Singapore and Indonesia are geographically close, so that Indonesia's export tariffs to Singapore are relatively small. Indonesia's main interest is that Indonesia needs Singapore as the main export market for cloves because through Singapore Indonesia can reach other markets such as Tanzania and Madagascar to avoid import duties into the country.Keywords: Clove, International Cooperation, National Interest, Commodity, International Political Economy